2022
DOI: 10.1002/dad2.12302
|View full text |Cite
|
Sign up to set email alerts
|

Men and women show partly distinct effects of physical activity on brain integrity

Abstract: Introduction Physical inactivity and female sex are independently associated with increased Alzheimer's disease (AD) lifetime risk. This study investigates the possible interactions between sex and physical activity on neuroimaging biomarkers. Methods In 134 cognitively unimpaired older adults (≥65 years, 82 women) from the Age‐Well randomized controlled trial (baseline data), we investigated the association between physical activity and multimodal neuroimaging (gray ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
(110 reference statements)
1
4
0
Order By: Relevance
“…We observed that higher PA was associated with lower amyloid burden; however, in sensitivity analyses, we found that the statistical significance of this association was driven by few men. Nevertheless, this finding would correspond to a recent study that also reported a significant association between amyloid burden and PA in men but not in women 49 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that higher PA was associated with lower amyloid burden; however, in sensitivity analyses, we found that the statistical significance of this association was driven by few men. Nevertheless, this finding would correspond to a recent study that also reported a significant association between amyloid burden and PA in men but not in women 49 …”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, this finding would correspond to a recent study that also reported a significant association between amyloid burden and PA in men but not in women. 49 We want to address some caveats regarding the interpretation of our results. As with all cross-sectional studies, we cannot provide direct causal evidence for protective roles of the studied lifestyle-related factors.…”
Section: Discussionmentioning
confidence: 98%
“…The vast majority of studies indicate that men have higher levels of physical activity than women, which may be due to different uses of the time available in the course of a day [33][34][35][36]. A nationwide study reported that, on average, men devote one hour and thirty-three minutes per day to sports, while women, on average, perform physical exercises for one hour and nineteen minutes per day.…”
Section: Of 22mentioning
confidence: 99%
“…Moreover, men's workouts tend to be characterized by higher intensity than those performed by women. As a result, men's higher physical activity, to a greater extent than women's, may be a factor in protecting their mental fitness [35,36].…”
Section: Of 22mentioning
confidence: 99%
See 1 more Smart Citation